PERAN KEPEMIMPINAN WANITA DI ERA MODERN - Cahayaningsih, Ica Putri (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
Abstract: This research is done to knowthe role of women leadership in the modern era. Which is still going through a lot of controversies. Anda different leadership styles between men and women. The study uses the method of library research or its library. to conduct identification systematically analyze documents and written materials that contain information. That deals with the women’s leadership problems especially in modern era. The result of this study was that the characteristic of feminism and masculinity when leading. The strong-necked, systematic, intuitive, sensitive characteristics of fenimism to others strongly support women’s leadership styles. although women do not adopt men’s thinking, but women also cannot avoid the gentleness that they have.